Trends in frequency of surgical procedures at Department of Otorhinolaryngology and Maxillofacial Surgery of Mostar University Hospital, Bosnia and Herzegovina (2013-2017) - Boris Jelavić; Dino Oršolić; Vlado-Vlaho Ćubela; Tomislav Sušac; Josip Lesko; Miro Leventić (Medicinski glasnik, 2019)
Aim: To determine whether there has been a change in frequency of selected otorhinolaryngology-head and neck surgical procedures during a 5-year period. Methods: Comparative cross-sectional analyses of surgical candidates and procedures performed at the Department of Otorhinolaryngology and Maxillofacial Surgery during the period 2013-2017 were done. Data on patients' demographics and cases of selected surgical procedures were extracted from the operating room log books. Patients' average age, male:female ratio, and the percent share of all surgical procedures for each selected surgical procedure for each studied year were calculated. Results: In comparison with the year 2013, the year 2017 showed no significant difference in age or sex of patients who underwent selected surgical procedures, increase of the number of all operations and the number of investigated selected operations, increase in the share of tonsil surgery, nasal septum and pyramid surgery, nasal polyposis surgery, parathyroid gland surgery, otoplasty, cochlear implantation, laryngeal surgery, and tracheotomy, and decline in the share of thyroid gland surgery, middle ear microsurgery, neck dissection, surgery of parotid gland, and surgery of neck cysts. Conclusion: Our finding of variations in utilization of some studied procedures provides a basis for future discussions, research and provision of health care services. Used data are specific to two studied cantons and do not represent a nationally representative database. The generalisability of the present results to Bosnia and Herzegovina as a whole might be limited. Therefore, similar future investigations conducted in other large hospitals in our country are warranted.
Keywords: head; neck; incidence; operative procedures; otorhinolaryngology